Affordable Electric Vehicles: Their Role in Meeting the U.S. Contribution to the Paris Climate Goals - Graham, John D.; Brungard, Eva (Frontiers in Environmental Science, 2022)
The United States government established a national goal of 50% plug-in vehicle penetration of the new light-duty vehicle fleet by 2030. Achievement of this goal is required to satisfy the country’s commitments to greenhouse-gas control under the 2015 Paris climate accords. Based on a market analysis of historical sales patterns, current and planned plug-in vehicle offerings, and sales forecasts for 2030, this article concludes that the US is unlikely to meet the 2030 goal without rapid commercialization of affordable plug-in vehicles, where affordable is defined as a price less than $45,000 per vehicle. Public policies are reviewed, in part based on European experience, that can accelerate the commercialization of affordable plug-in vehicles in the United States.